Terminology of Dental Caries and Dental Caries Management: Consensus Report of a Workshop Organized by ORCA and Cariology Research Group of IADR (2019)
A 2-day workshop of ORCA and the IADR Cariology Research Group was organized to discuss and reach consensus on definitions of the most commonly used terms in cariology. The aims were to identify and to select the most commonly used terms of dental caries and dental caries management and to define them based on current concepts. Terms related to definition, diagnosis, risk assessment, and monitoring of dental caries were included. The Delphi process was used to establish terms to be considered using the nominal group method favored by consensus. Of 222 terms originally suggested by six cariologists from different countries, a total of 59 terms were reviewed after removing duplicates and unnecessary words. Sixteen experts in cariology took part in the process of reaching consensus about the definitions of the selected caries terms. Decisions were made following thorough "round table" discussions of each term and confirmed by secret electronic voting. Full agreement (100%) was reached on 17 terms, while the definitions of 6 terms were below the agreed 80% threshold of consensus. The suggested terminology is recommended for use in research, in public health, as well as in clinical practice.